Serial right ventricular assessment in patients with hypoplastic left heart syndrome patients (HLHS): a cardiovascular magnetic resonance study. (8th February 2021) - Sobh, M; Gabbert, D; Uebing, A; Voges, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with hypoplastic left heart syndrome (HLHS) are at risk for right ventricular (RV) dysfunction over the course of the three-stage surgical palliation with the final step being the completion of the total cavopulmonary connection (TCPC). However, less is known about RV function during follow-up after TCPC completion. We assessed RV function by analysing serial cardiovascular magnetic resonance (CMR) studies in a large cohort of HLHS patients. Methods: CMR studies from 95 HLHS patients (67 males) were retrospectively analysed. Short axis cine images were used to measure RV end systolic and end diastolic volumes and ejection fraction (RVEF). Oblique cine images showing the atria and right ventricle in a similar manner like a standard "4-chamber view" were used to measure tricuspid annular plane systolic excursion (TAPSE) and long axis strain (LAS). Results: From the 95 patients, all had at least two and 32 patients had three CMR scans. The first scan was performed at a mean age of 4.9 ± 2.8 years, the second scan at a mean age of 9.3 ± 4 years and the third at a mean age of 14.3 ± 3.7 years. The mean values of RV end diastolic and end systolic volume indexed to body surface area (REDVi, RVESVi) as well as RV ejection fraction (RVEF) at the three time points were: 1) REDVi 92.6 ± 21.9 ml/m2, RVESVi 43 ± 15.1 ml/m2, RVEF 54.2 ± 7.1%; 2) REDVi 93.9 ± 25.6 ml/m2, RVESVi 44.6 ± 18.3 ml/m2, RVEF 53.6 ± 7.8%; 3) REDVi 110.9 ± 41.9 ml/m2, RVESVi 58.1 ± 35 ml/m2, RVEF 50.1 ± 10.1%. There was a statistically significant increase in RVEDVi and RVESVi from the first and the second scan to the third scan (p < 0.01). RVEF was lower at the time of the third scan compared to the first and second scan, but this difference was not statistically significant. TAPSE increased slightly from the first to the third scan (p < 0.05). There was no change in stroke volume and LAS from the first to the third scan. Strong correlations were found between RVEF and LAS as well as between RVEF and TAPSE (r = 0.49 and r=-0.50; p < 0.001, respectively). Conclusion: Serial assessment of CMR studies in HLHS patients after TCPC completion could demonstrate an increase in indexed RV volumes over time, whereas RV stroke volume, RVEF and LAS largely remain stable.